THE ROLE OF ENTREPRENEURSHIP EDUCATION ON THE ENTREPRENEURIAL INTERESTS OF PRIVATE UNIVERSITY STUDENTS IN THE CITY OF SERANG: PERAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA UNIVERSITAS SWASTA DI KOTA SERANG - Saripudin Saputra; Andi Hasryningsih Asfar (Yayasan Education and Social Center, 2022)
The purpose of this study was to determine the effect of entrepreneurship education on the entrepreneurial interest of private university students in Serang City. The variables of this research are entrepreneurship education as an independent variable and interest in entrepreneurship as the dependent variable. Quantitative research uses a correlational approach. The population of this research is 25,094 private university students in Serang City with 4 private universities. The sample used the sampling method suggested by Hair, et al so that the sample size was 5 x 40 = 200 so that the total sample was 200 respondents. The findings of this study reveal that Hypothesis 1 obtained a path coefficient value of 0.334 with a t-statistic value of 3.177 > 1.96 so that entrepreneurship education has an effect on interest in entrepreneurship